Co to jest „krytyczne" prawo rodzinne - Eekelaar, John (Wydział Prawa i Administracji UAM, 1989)
A growing segment of British legal literature, identified by the label Critical Legal Studies UK might be explained as a delayed reflection of the „movement" of that name originating in the United States. The purpose of this article is to attempt an assessment of the value which a „critical" approach might hold for English family law. It is not easy to capture the essential thread of critical legal studies. „Critical" legal writers would reject a view of law which saw legal decisions as formal deductions from established premises, and systems of law as emanations of systems of values which have inherent, objective validity. Instead, the „critical" legal conclusion — scarcely a revelation — is that the law is „inextricably mixed in the totality of social relations and institutions". As far as family law is concerned, „critical" legal writers would claim that „at the root of a critical theory is the, public/private dichotomy". The author questions the usefulness of that dichotomy as a tool of contemporary legal analyses. Then, he tries to prove that one feature of „critical" legal theory not shared by "non-critical (liberal)" theory is that the critical writer inserts an explicit ideological stance into his or her legal analysis. If this is so — claims the author — the "critical" approach reverts to a political programme, and is jurisprudentially irrelevant. If the "critical" writer is less concerned about exploring the doctrinal and empirical problems of achieving coherence within the multitude of legal and institutional mechanisms and is surer of the answers to the value-conflicts than the "non-critical" scholar, i.e. if his/her "currency is commitment rather than truth", one may truly ask whether the movement has appropriated to itself theepithet "critical" under false pretences.
What is „critical" family law